The immunomodulatory effects of rolipram abolish drug-resistant latent phase of Toxoplasma gondii infection in a murine model. Issue 2 (June 2015) - Afifi, Mohammed A.; Al-Rabia, Mohammed W.
Abstract: Background: Latent toxoplasmosis always has the risk of reactivation leading to significant sequelae. The available medications, for chronic toxoplasmosis, are awfully limited by resistance of Toxoplasma cysts. Therefore, there is a growing necessity for novel therapeutic approaches. Agents increasing cAMP levels and downregulating proinflammatory cytokine could inhibit Toxoplasma conversion to the bradyzoite stage. This study explores a potential immunomodulatory effect of rolipram, a PDE4 inhibitor, on the course of experimental toxoplasmosis and links this role to deterrence of the resistant chronic phase of the disease. Materials and methods: Mice infected with low pathogenic strain of Toxoplasma gondii were treated with rolipram for three weeks. The effect of rolipram was evaluated through tissue injury scoring, brain cyst count, specific IgG titers as well as TNF-α, IFN-γ and IL-12 assays. Results: Rolipram was partially able to prevent the progression to chronic toxoplasmosis. Toxoplasma brain cyst burden showed a 74% reduction while Toxoplasma -induced inflammatory foci per liver area and nucleated cells per inflammatory focus were significantly reduced: 57.14% and 61.3% respectively. Significant reduction of TNF-α (84.6%), IFN-γ (76.7%) and IL-12 (71%) levels was demonstrated along with significant inhibition of anti- Toxoplasma antibody response. Conclusion: Rolipram efficiently modulated the Toxoplasma -induced immunological changes with a consequent remission of chronic toxoplasmosis. This study is the first to report the utilization of PDE4 inhibitors as possible immune modulators of chronic phase of Toxoplasma infection.